Fr Mažvydas, Žemaitija and the Gniezno Consistory Court of Appeal, 1525–1539 - S.C. Rowell (Acta Historica Universitatis Klaipedensis, 2017)
By the late fifteenth century, more notably after 1477, appeal cases from Catholics in the Grand Duchy of Lithuania began to appear before the Consistory Court in Gniezno in increasing numbers. These cases involved quite a wide social group, and dealt with a broad range of issues (not just matrimonial disputes or the hiring out of parish churches between priests). Appellants came before the judges from across the Grand Duchy. This article covers cases from 1524 to 1539. Even when court material gives few details of cases, it can help solve issues of parish church and chantry foundations and patronage. The most striking feature of the records between 1524 and 1538 is the predominance of cases from Žemaitija, a diocese which previously featured only in disputes involving the bishop. This confirms the deepening of Catholic practice across the diocese of Medininkai (Žemaitija) as reflected in particular in the increasingly predominant use of Christian forenames from the last quarter of the fifteenth century. Most interesting perhaps for those studying the rise of Protestantism in Lithuania will be the occurrence of one Fr Andriejus Mažvydas, parish priest of Alsėdžiai, among the appellant litigants of 1536. This information about a very probable kinsman (uncle, cousin, brother?) of Martynas Mažvydas offers new insights into the Lutheran’s family background and geography.